Transport science and technology - Goulias, Konstadinos G. (Emerald, 2006)
The book will offer a representative sample of the best papers presented at the Transport Science and Technology Congress (TRANSTEC) Athens 2004. It will also serve as the peer reviewed conference proceedings. As in the congress writing, in this book our aim is to demonstrate the most recent developments in merging scientific and technological discoveries to solve important transportation problems and to cover a wide variety of transportation issues in passenger and freight transportation but also a variety of modes. A parallel aim is to have papers that are representative of the research and development around the world. The chapters will be from the Americas (North and South), Asia, and Europe. The draft outline is organized into four parts. The first part will contain an overview and review papers from the keynote speakers and most likely one additional paper in the new area of human attention and microsleeps from a special paper session organized the Czech Technical University. The second part of the book will contain contributions from policy and planning and will span all modes of transportation and include both passenger transport and freight. In the third part, a selection of papers from traffic engineering and management will contain papers on new measurement techniques, traffic engineering parameters that can be measured more precisely with technology, and applications of information and communication technologies. The fourth part of the book will contain a series of papers illustrating the preparation of Athens for the Olympics and will contain papers that span from the preliminary planning to the operations of information and communication systems as well as the management of the public transportation system and its components. All papers will be peer-reviewed following the guidelines of the journal, "Transportation Research" to assure innovation in methods but also relevance to the subject matter. It adopts a global perspective with papers from the Americas, Asia and Europe. It is organized into four parts; all articles are peer-reviewed.
Keywords: Transportation -- General.; Transport industries.; Transport technology & trades.; Transportation -- Research.; elektronické knihy; electronic books